Implementasi Pembelajaran Contextual Teaching And Learning Bagi Warga Emas Dalam Upaya Membentuk Insan Kamil Di Madrasah Pertubuhan Kebajikan Al-Muhibbin Malaka Malaysia - Nasution, Khairil Anwar Nasution; Abrianto, Danny; Fadillah, Hari Hikmatul; Firdaus, Muhammad Iqbal; Rafbani, Burhannuddin (Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to describe and analyze the Implementation of Contextual Teaching and Learning for Senior Citizens in an Effort to Form Perfect Insan at the Al-Muhibbin Virtue Development Madrasah, Melaka, Malaysia. This study uses a descriptive qualitative approach with a pedagogical perspective. Data collection techniques include observation, in-depth interviews, and documentation. The collected data are analyzed systematically through the stages of data reduction, data presentation, and verification to draw conclusions. The results of this study indicate that contextual teaching and learning for senior citizens in an effort to form perfect insan at the Al-Muhibbin Virtue Development Madrasah, Melaka, Malaysia in the learning process is reflected in the learning steps in the classroom which show that the components of the contextual strategy are implemented and the impact of the implementation of TCL learning in the learning process leads to increased learning motivation, enthusiasm for learning, student activity, student appreciation of learning materials, and character formation of students through learning relevant Islamic Religious Education materials.